LABOR ABSORPTION FACTORS OF MICRO, SMALL, AND MEDIUM ENTERPRISES (SMES) IN SUMATRA ISLAND: PANEL DATA ANALYSIS FOR THE 2020–2024 PERIOD - Inda Arfa Syera; Hajar Affiah; Faulia Anggeraini; Dewi Hakiki (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The purpose of this study is to analyze the influence of the number of Micro and Small Industries (MSMEs), the value of MSME output , and GRDP on the absorption of MSME labor in 10 (ten) provinces on Sumatra Island for the period 2020–2024. This study uses panel data with a Fixed Effect Model (FEM) approach. The results of the study revealed that the number of MSME businesses significantly influences the absorption of MSME labor (β = 1.914200 ; p < 0.05), while the value of MSME output (β = 0.001026 ; p > 0.05) and GRDP (β = 0.103498 ; p > 0.05) do not significantly affect the absorption of MSME labor. The model explains 99.2364% of the variation in MSME labor absorption (Adjusted R² = 0.992364 ). The findings of this study are that the expansion of employment opportunities is more determined by the growth in the number of business units than by the increase in output or the size of the regional economy. The government should prioritize policies that encourage the formation of new MSME business units and provide training and access to capital to increase business capacity without reducing employment.